2013
DOI: 10.1007/978-1-62703-441-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Expression and Functional Testing of Candidate Adenylate Cyclase Domains

Abstract: Adenylate cyclases (ACs) are enzymes capable of converting adenosine-5'-triphosphate to cyclic 3', 5'--adenosine monophosphate (cAMP). In animals and lower eukaryotes, ACs and their product cAMP have firmly been established as important signalling molecules with important roles in several cellular signal transduction pathways. However, in higher plants, the only annotated and experimentally confirmed AC is a Zea mays pollen protein capable of generating cAMP. Recently a number of candidate AC-encoding genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…1C). 13,14 To analyze the involvement of NbAC on TβL-induced necrotic wildfire lesions, we created NbAC-silenced N. benthamiana. Results of qRT-PCR analysis suggested that NbAC was well-silenced ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1C). 13,14 To analyze the involvement of NbAC on TβL-induced necrotic wildfire lesions, we created NbAC-silenced N. benthamiana. Results of qRT-PCR analysis suggested that NbAC was well-silenced ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Plant AC has been isolated and enzymatic properties were also analyzed in Zea mays and A. thaliana, indicating AC is in plants. 13,14 In this study, we isolated AC (NbAC) from N. benthamiana (Fig. 1A,B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assmann, 1995;Gehring, 2010) further supporting the role of cAMP in plant signaling cascades. However, to-date only few ACs have been experimentally tested in higher plants; these include a Zea mays protein that participates in polarized pollen tube growth (Moutinho et al, 2001), a Nicotiana benthamiana protein with a role in tabtoxinine-β-lactam-induced cell death (Ito, 2014), a Hippeastrum x hybridum protein that is involved in stress signaling (Świeżawska et al, 2014), an Arabidopsis pentatricopeptide repeat-containing protein, AtPPR (At1g62590) (Ruzvidzo et al, 2013), an Arabidopsis clathrin assembly protein with a predicted role in actin cytoskeletal remodeling during endocytic internalization (Chatukuta et al, 2018) and an Arabidopsis K + -uptake permease (KT/HAK/KUP7; AtKUP7, At5g09400; Al-Younis et al, 2015). One possible reason for this apparent elusiveness is the evolutionary divergence of plant nucleotide cyclases where only key amino acids within the catalytic centers appear to be retained.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, not much is known in higher plants about ACs or their product cAMP as is in animals and lower eukaryotes although currently, there are already four experimentally tested and functionally confirmed ACs in plants. These are the Zea mays pollen signaling protein responsible for the polarized pollen tube growth (Moutinho et al, 2001), the Arabidopsis thaliana pentatricopeptide repeat protein responsible for pathogen responses and gene expressions (Ruzvidzo et al, 2013), the Nicotiana benthamiana adenylyl cyclase protein responsible for the tabtoxinine-β-lactam-induced cell deaths during wildfire diseases (Ito et al, 2014), and the Hippeastrum hybridum adenylyl cyclase protein involved in stress signaling (Swiezawska et al, 2014).…”
Section: Introductionmentioning
confidence: 99%